Frequency dependence of the coercive field of 0.71Pb(Mg(1/3)Nb(2/3))O(3)-0.29PbTiO(3) single crystal from 0.01 Hz to 5 MHz - Chen, Zhaojiang (Appl Phys Lett, 2017)
The frequency dependence of the coercive field E(c) in [001](c) poled 0.71Pb(Mg(1/3)Nb(2/3))O(3)–0.29PbTiO(3) single crystals was investigated as a function of frequency f from 0.01 Hz to 5 MHz. E(c) was found to be proportional to [Formula: see text] as predicted by the Ishibashi and Orihara model, but our results showed two frequency regimes separated at around 1.0 MHz with different β values. This change of switching kinetics may be due to the presence of slower relaxation times for non–180° domain switching and heterogeneous nucleation of polar nanoregions, whose contribution to polarization reversal is frozen out beyond 1.0 MHz, leading to a larger β.